Central Asia and Its Asian Neighbors Security and Commerce at the Crossroads - Lal, Rollie (RAND Corporation, 2006)
China, Iran, Afghanistan, India, and Pakistan are critical players in the security and economic issues that will determine the future of Central Asia and affect U.S. interests in the region. By assessing the developing relations between Central Asia and its neighbors, it is evident that each country stands to benefit from stability and economic growth in Central Asia, but opinion toward U.S. presence and policy in the region could be a point of conflict.